Orthogonally functionalized donor/acceptor homo- and heterodimeric dyes for dye-sensitized solar cells: an approach to introduce panchromaticity and control the charge recombination - Sil, Manik Chandra; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Punitharasu, Vellimalai; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Organic dyes possessing conjugated pi-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular pi-pi interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-1-D-1, and D-2,-D-2) and heterodimeric (D-1-D-2 and D-2-D-4) donor/acceptor (D/A) dyes containing spiroBiProDOT pi-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation reaction and correlates the device performance with monomeric dyes (D-1 and D-2). Both the thiophenes (pi-spacer) of spiroBiProDOT were functionalized with same or different donor groups which led to homodimeric and heterodimeric chromophores in a single sensitizer. The homodimeric spirodye D-1-D-1 showed higher power conversion efficiency (PCE), of 7.6% with a V-oc and J(sc) of 0.672 V and 16.16 mA/cm(2), respectively. On the other hand, the monomeric D-1 exhibited a PCE of 3.2% (V-oc of 0.64 V and J(sc) of 7.2 mA/cm(2)); which is lower by 2.4 fold compared to dimeric analogue. The spiro-unit 20 provides flexibility between the incorporated chromophores to orient on TiO2 due to four sp(3)-centers, which arrest the molecular motions after chemisorption. This study shows a new molecular approach to incorporate two chromophores in the dimeric dye possessing complementary absorption characteristics toward panchromatic absorption. The attenuated charge recombination at TiO2/Dye/redox couple interface in case of D-1-D-1, owing to better passivation of TiO2 surface, was elucidated through impedance analysis. The FT-IR spectrum of D,-D, adsorbed on TiO2 film indicated both the carboxylic units were involved in chemisorption which makes strong coupling between dye and TiO2.